Gene bank scheduling of seed regeneration: Interim report on a long term storage study - Robert Redden; Debra Partington (Journal of Integrative Agriculture, 2019)
A major challenge for the management of gene banks is the maintenance of good seed health in the collections. Large germplasm collections >10 000 accessions often have been acquired from different sources over a range of dates, may differ in germination at time of deposition in the gene bank, and may have genetic differences in seed longevity. The major storage variables affecting seed longevity are temperature and seed moisture content. Two varieties of each pea (Pisum sativus L.), lentil (Lens culinaris Medikus subsp. culinaris), and chickpea (Cicer arietinum L.), were stored at three temperatures; 40, 20, and 2°C, each with three seed moisture levels of 10.9–13.8% (high), 7.9–10.3% (medium), and 7–7.8% (low), in the Australian Temperate Field Crops Collection gene bank. Seed longevity at a given storage period was estimated by the corresponding germination percentage for each treatment. This paper is an interim report on seed viability decline in the first seven years of this seed longevity study, in which viability decline towards zero was almost completed in the three seed moisture treatments at 40°C and the 20°C high seed moisture treatment, but had not declined in the other treatments. Seed longevity positively responded to a reduction in temperature and then to a reduction in seed moisture. The number of days in storage for seed germination decline to 85% (p85), and to 50% (p50) for mean seed viability, are reported by storage/varietal treatment. Both p85 and p50 showed significant inverse linear responses with seed moisture at 40°C for pea and lentil varieties, with intra-specific variation for pea. This long term trial aims to provide informed timing of seed regeneration for accessions in a gene bank.